2009
DOI: 10.1080/00036840701522861
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of housing price volatility in Canada: a dynamic analysis

Abstract: This article tries to identify the determinants of housing price volatility and to examine the dynamic effects of these determinants on volatility using quarterly data for Canada. The Generalized Autoregressive Conditional Heteroskedastic (GARCH) and the Vector Autoregressive (VAR) models have been employed to analyse possible time variation of the housing price volatility and the interactions between the volatility and the key macroeconomic variables. We find the evidence of time varying housing price volatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 17 publications
6
50
0
Order By: Relevance
“…In other words, a negative shock would raise the uncertainty and volatility of these markets dramatically. These results are also consistent with Miles (2008) in the U.S. housing market and Hossain and Latif (2007) in the Canada market,…”
Section: (Insert Table 6)supporting
confidence: 81%
See 1 more Smart Citation
“…In other words, a negative shock would raise the uncertainty and volatility of these markets dramatically. These results are also consistent with Miles (2008) in the U.S. housing market and Hossain and Latif (2007) in the Canada market,…”
Section: (Insert Table 6)supporting
confidence: 81%
“…Additionally, the estimated volatility series with a GARCH model is Granger-caused by the home appreciation rate and Gross Metropolitan Product (GMP) growth rate. More recently, Hossain and Latif (2007) have also offered the evidence of time varying housing price volatility in the Canadian housing market. The results also demonstrated that the gross domestic product growth rate, house price appreciation rate and inflation are the determinants of house price volatility with using an impulse responses analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sivitanides (2015) verified the effect of GDP per capita, as well as the effect of the number of households and construction costs on Cyprus house prices over the period 2006-2014. That study also verified a structural break in the effect of GDP over the period immediately following the beginning of the global financial crisis. Hossain and Latif (2009), in a study of the intertemporal behaviour of house prices in Canada, also verified the effect of GDP on house prices, and particularly on house price volatility. Furthermore, their study revealed an asymmetric effect of GDP on house price volatility.…”
Section: Macroeconomic Determinants Of House Pricesmentioning
confidence: 66%
“…The ARCH/GARCH methodologies by Bollerslev (1986) and Engle (1982), as well as the SV model (Taylor, 1994), attempt to simulate this empirical phenomenon in financial markets. Indeed, the Univariate Stochastic Volatility (USV) models and ARCH-type models use alternatively in accounting for both conditional and unconditional properties of volatility (Kim et al, 1998;Shephard, 2004;Gerlach and Tuyl, 2006;Hossain and Latif, 2009;Tsai et al, 2010).…”
Section: Methodsmentioning
confidence: 99%